Analisis Kualitas Pelayanan Publik E-KTP di Dinas Kependudukan dan Pencatatan Sipil (DISDUKCAPIL) Kabupaten Gayo Lues - Rafika Duri; R Hamdani Harahap; Isnaini Isnaini (Mahesa Research Center, 2022)
The purpose of this paper is to analyze the quality of public services and the two factors that hinder the E-KTP service at the Department of Population and Civil Registration of Gayo Lues Regency. The method used in this research is descriptive with qualitative research instruments with observations, documentation studies and interviews. While the data analysis used descriptive analysis. The results showed that the quality of E-KTP public services which refers to Zeithaml's theory of tangible dimensions (physical evidence/infrastructure), reliability (reliability), responsiveness (responsiveness), assurance (guarantee), empathy (empathy) shows, the quality of public services The e-KTP at the Population and Civil Registration Office of Gayo Lues Regency has been running but is still not good or still not optimal. The inhibiting factors for E-KTP public services at the Disdukcapil include inadequate human resources, limited financial resources, inadequate facilities and infrastructure, and lack of employee commitment. To improve the quality of public services, the E-KTP Disdukcapil must improve infrastructure, place employees according to competence, increase employee discipline, and in service there should be no discrimination and prioritize service users/community.